2020
DOI: 10.21608/ejfsat.2020.20565.1118
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and Foramen Magnum Variables for sex determination in Egyptians using computed Tomographic Images

Abstract: Introduction: Sex determination is one of the principle indicators of identity. The skull is the second best part of the skeleton to be used for sex determination after the pelvis. Sex determination from cranial fragments becomes essential especially when only a part of the skull is brought for identification. Aim: The present study was aimed to demonstrate the sexual dimorphism of the orbit and the foramen magnum (FM) in a sample of Egyptian population in order to increase the number of parameters used for id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…However, in the studies performed by Hosseini et al, Slima et al and Abo El-Atta et al on Iranian and Egyptian populations the FM index had a significant difference between the two sexes. 23,24,27,30 The current study revealed that the mean length and width of FM is males in (36.71, 31.83mm) and (35.11, 30.26mm) (32.18, 27.20mm). 23,24 The mean values for FM length & width in males and females were higher in our study compared to the same measurements in the Indian, English & Turkish populations.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…However, in the studies performed by Hosseini et al, Slima et al and Abo El-Atta et al on Iranian and Egyptian populations the FM index had a significant difference between the two sexes. 23,24,27,30 The current study revealed that the mean length and width of FM is males in (36.71, 31.83mm) and (35.11, 30.26mm) (32.18, 27.20mm). 23,24 The mean values for FM length & width in males and females were higher in our study compared to the same measurements in the Indian, English & Turkish populations.…”
Section: Discussionsupporting
confidence: 49%
“…23,24,27,30 The current study revealed that the mean length and width of FM is males in (36.71, 31.83mm) and (35.11, 30.26mm) (32.18, 27.20mm). 23,24 The mean values for FM length & width in males and females were higher in our study compared to the same measurements in the Indian, English & Turkish populations. However, higher values were recorded by Edwards et al in their study on Swiss population.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation